2013
DOI: 10.1016/j.memsci.2012.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of membrane fouling on N-nitrosamine rejection by nanofiltration and reverse osmosis membranes

Abstract: Open and solid symbol indicates the result of the first and second experiment, respectively. The impact of fouling on N-nitrosamine rejection by nanofiltration (NF) and reverse osmosis 2 (RO) membranes was investigated in this study. Membrane fouling was simulated using 3 tertiary treated effluent and several model fouling solutions (that contained sodium alginate, 4 bovine serum albumin, humic acid or colloidal silica) to elucidate the changes in rejection 5 behaviour of N-nitrosamines. In general, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 36 publications
6
39
0
Order By: Relevance
“…Once fouled, the membrane surface was covered with the foulant and the surface hydrophobicity of the fouled membrane reflects the hydrophobicity of the foulant itself [35]. Changes observed in the membrane surface hydrophobicity due to humic acids, sodium alginate and secondary treated effluent fouling are consistent with data previously reported by Fujioka et al [27]. Silica colloids are quite hydrophilic due to their negatively charged silanol groups [36].…”
Section: Hydrophobicitysupporting
confidence: 86%
See 1 more Smart Citation
“…Once fouled, the membrane surface was covered with the foulant and the surface hydrophobicity of the fouled membrane reflects the hydrophobicity of the foulant itself [35]. Changes observed in the membrane surface hydrophobicity due to humic acids, sodium alginate and secondary treated effluent fouling are consistent with data previously reported by Fujioka et al [27]. Silica colloids are quite hydrophilic due to their negatively charged silanol groups [36].…”
Section: Hydrophobicitysupporting
confidence: 86%
“…The hydrodynamic diameter of the Ludox HS30 silica colloids was estimated to be approximately 9 nm [26]. By contrast, molecular weights of the humic acid and sodium alginate were in a range 12 -80 and 1 -100 kDa, respectively [27].…”
Section: Selected Model Foulantsmentioning
confidence: 95%
“…This can also be supported by other experimental results using various model foulants in which the impact of model foulants (i.e. sodium alginate, humic acid, bovine serum albumin, colloidal silica) on N-nitrosamine rejection was minor or negligible [47]. These model foulants are larger in size than the free-volume hole-size of the membrane active skin layer and has a relatively narrow size distribution.…”
Section: Membrane Foulingsupporting
confidence: 71%
“…Fujioka et al [47] evaluated the effects of membrane fouling using tertiary treated wastewater and reported that membrane Fujioka et al [47] suggested that the increased rejections could have been caused by the restriction of compound pathway (e.g. free-volume holes of the active skin layer) with small foulants, improving the size exclusion effect on compound rejection.…”
Section: Membrane Foulingmentioning
confidence: 99%
“…200 µL) will allow for detailed investigations of the fate of NDMA including NDMA formation and removal during water reclamation at laboratory scale. In fact, the limitation of providing a large number of samples for SPE-GC-MS/MS analysis significantly limited the number of sampling occasions in a previous laboratory-scale fouling study (Fujioka et al, 2013a). This study aimed to establish an HPLC-PR-CL analytical method that is fast and reliable for NDMA analysis during potable water reuse.…”
Section: Introductionmentioning
confidence: 99%